Chemical constituents and biological activities of Clausena excavata and some citrus species (Rutaceae) - Peh, Tian Hai (2001)
Investigations on the leaves and stem bark of Clausena excavata (Rutaceae) have resulted in the isolation of twelve compounds. The structures of these compounds were elucidated b y using spectroscopic techniques such as NMR, MS, IR and UV and also by comparison with previous reports. The stem bark of C. excavata collected from Jabi, Kedah yielded two new carbazole alkaloids, 1,8-dihydroxy-3-fonnyl-4-prenylcarbazole and 3- carbomethoxy-2-hydroxy-7 -methoxycarbazole, three known carbazole alkaloids, c1ausine-H, cIausine-K and cIausine-B together with one coumarin, scopoletin, two hmonoids (cIausenarin and CEA 10), and one triterpene, stigmasterol. From the leaves of C. excavata, a known carbazole alkaloid, 3-formyl-2 ,7- dimethoxycarbazole together with l3-sitosterol and safrole were isolated. The essential oils were obtained by hydrodistillatio n using fresh leaves and analysed using GC-MS spectrometry. The main essential oil components from Clausena excavata (Jabi A) were safrole and a-terpinolene, while Jabi B gave safrole and terpinolene as major constituents. The essential oils from several species of Citrus of Malaysia have also been investigated. Citronellal and citronellol were the major components of C. hystrix. The major constituents of C. aurantifolia were limonene, (z)-citral and (e)-citral. The major components of the oils of C. sinens is were found to be linalool and b-elemene . Germacrene-D, elernol and b-eudesmol were the major constituents of the oil of C. microcarpa. The oil of C. maxima (Kedah) contained significant amounts of sabinene, y-terpinene and